Cover Feature: 2‐Phenyloxazole‐4‐carboxamide as a Scaffold for Selective Inhibition of Human Monoamine Oxidase B (ChemMedChem 18/2019). (17th September 2019) - Di Paolo, Maria L.; Christodoulou, Michael S.; Calogero, Alessandra M.; Pinzi, Luca; Rastelli, Giulio; Passarella, Daniele; Cappelletti, Graziella; Dalla Via, Lisa
Abstract : The Cover Feature shows the steeplechase of a new promising inhibitor of monoamine oxidase B (MAO‐B), a pharmacological target for the treatment of neurodegenerative disorders, such as Parkinson's disease. The 2‐(2‐hydroxyphenyl)‐ N ‐phenyloxazole‐4‐carboxamide (compound4a ) participates in the race, jumping over the most important obstacles to become a successful model for the development of novel drugs targeting MAO‐B. The first obstacle is effectiveness as a MAO‐B inhibitor, the second is represented by the selectivity towards the MAO‐B isoform, and the third is the safety for NGF‐differentiated PC12 cells. More information can be found in the Full Paper by Lisa Dalla Via et al. onpage 1641 in Issue 18, 2019 (DOI:10.1002/cmdc.201900261 ).